Analisis Peran Guru dalam Penguatan Profil Pelajar Pancasila (P5) Sebagai Upaya Pengembangan Karakter Siswa Kelas 3 di SDN Kestalan - Fivin Anjani; Mahardika Putri Buana; Adellisa Alya Avrillita; Endrise Septina Rawanoko (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the role of teachers in strengthening the Pancasila Student Profile (P5) as an effort to develop the character of third-grade students at SDN Kestalan. Strengthening P5 is an essential component of the Merdeka Curriculum because it functions to shape students’ character holistically through six main dimensions. However, the implementation of P5 in elementary schools still faces several challenges, such as uneven teacher understanding, less structured planning, and diverse student characteristics. This research uses a qualitative descriptive approach with observation, interview, and documentation techniques to obtain in-depth data on teacher practices, integration strategies, obstacles, and the impact of P5 implementation. The results show that teachers have an adequate understanding of the P5 concept and strive to integrate it through interactive lectures, question-and-answer sessions, simple experiments, the habituation of the 5S culture, and creative projects that actively involve students. The obstacles encountered are generally related to discipline issues, emotional immaturity, limited facilities, and suboptimal parental involvement. However, these challenges can be reduced through personal approaches, positive motivation, support from school facilities, and collaboration with parents. The implementation of P5 has been proven to have a positive impact on students’ character development, especially in the aspects of politeness, cooperation, responsibility, and self-confidence. Therefore, the strategic role of teachers and the support of a conducive learning environment are key factors in the success of character strengthening through P5.